Golden era of radiosensitizers - Cizkova, Jana; Dolezal, Ondrej Jan; Buchta, Vojtech; Pospichal, Jan; Blanar, Vit; Sinkorova, Zuzana; Carrillo, Anna (Frontiers in Veterinary Science, 2024)
The past 30 years have brought undeniable progress in medicine, biology, physics, and research. Knowledge of the nature of the human body, diseases, and disorders has been constantly improving, and the same is true regarding their treatment and diagnosis. One of the greatest advances in recent years has been the introduction of nanoparticles (NPs) into medicine. NPs refer to a material at a nanometer scale (0.1–100 nm) with features (specific physical, chemical, and biological properties) that are broadly and increasingly used in the medical field. Their applications in cancer treatment and radiotherapy seem particularly attractive. In this field, inorganic/metal NPs with high atomic number Z have been employed mainly due to their ability to enhance ionizing radiation’s photoelectric and Compton effects and thereby increase conventional radiation therapy’s efficacy. The improvement NPs enable relates to their enhanced permeation ability and longer retention effect in tumor cells, capacity to reduce toxicity of commercially available cancer drugs through advanced NPs drug delivery systems, radiation sensitizers of tumors, or enhancers of radiation doses to tumors. Advanced options according to size, core, and surface modification allow even such multimodal approaches in therapy as nanotheranostics or combined treatments. The current state of knowledge emphasizes the role of gold nanoparticles (AuNPs) in sensitizing tumors to radiation. We have reviewed AuNPs and their radiosensitizing power during radiation treatment. Our results are divided into groups based on AuNPs’ surface modification and/or core structure design. This study provides a complete summary of the in vivo sensitizing effect of AuNPs, surface-modified AuNPs, and AuNPs combined with different elements, providing evidence for further successful veterinarian and clinical implementation.